Effectiveness of Biology Learning to Improve Digital Literacy and Higher Order Thinking Skills on the Concept of Digestive System - Nia Maulidhia Ibrahim; Yayan Sanjaya; Mimin Nurjhani (Postgraduate, University of Mataram, 2024)
The use of HOTS skill-based e-learning can be used as one of the ways to provide HOTS skills and digital literacy skills. This study aims to determine the effectiveness of HOTS-based e-learning in improving HOTS skills and digital literacy skills of high school students. This study used a quasi-experimental method. The research design used was non-equivalent control group design. The samples in this study were XI Science class students consisting of 38 people determined by purposive sampling technique. This research was conducted on two classes, namely the experimental class (learning using HOTS-based e-learning) and the control class (learning using e-learning not based on HOTS). The results showed that there was a significant difference in the mean between the experimental and control classes on digital literacy and higher order thinking skills. T test on the value of digital literacy skills of HOTS skills shows the number (2-tailed = 0.000 < α (0.05), which means that there is a difference in the effectiveness of using HOTS-based e-learning with e-learning not based on HOTS to improve students' digital literacy skills. Then the results showed that there was a significant difference in the average high-level thinking skills of students between the experimental class and the control class. Showing the T-test number on the value of digital literacy skills shows the number (2-tailed = 0.000) < α (0.05), it means that there is a difference in the effectiveness of using HOTS-based e-learning with ordinary e-learning to improve students' digital literacy skills. The N-Gain score criteria for using HOTS-based e-learning to improve digital literacy skills fall into the medium category (N-gain = 0.56) and the use of HOTS-based e-learning to improve higher order thinking skills in the medium category (N-gain = 0.83).